THE IMPACT OF TECHNOLOGICAL TRANSFORMATION ON CAREER CHOICES IN THE STEM SECTOR - Subasman, Iman; Rusmiati Aliyyah, Rusi (Jurnal Kajian Pendidikan dan Psikologi, 2023)
This study aims to analyse the influence of digital transformation on career aspirations in the STEM (Science, Technology, Engineering, and Mathematics) sector. Qualitative and quantitative data analysis methods were used to collect data from various educational institutions and technology companies. The results show that the adoption of digital technology in STEM education increases students' interest and competence in STEM subjects, which directly affects their career aspirations. The research also found that digital skills acquired through STEM education contribute significantly to job readiness in the STEM sector. In addition, the findings highlight the importance of project-based and collaborative learning enriched with digital technologies to prepare students for the changing work environment. This research contributes to the literature by providing insights into how STEM education, accompanied by digital transformation, can shape career aspirations in the STEM sector. Recommendations for education practitioners and policymakers include greater integration of digital technologies in STEM curricula and the development of teacher training programmes to teach with advanced technologies. Implications for career development in the STEM sector are also discussed, emphasising the importance of continuity between education and industry needs.